The Matrix, the Spiderweb and the influence diagram: Developments in systems thinking at the New Zealand customs service - Cavana, Robert; Clifford, Leslie (School of Management Working Papers, 1999)
This paper discusses the introduction of systems thinking concepts into the strategic planning process at New Zealand Customs Service (NZCS). The recent state sector reforms and restructuring at NZCS are briefly outlined. A Working Group of government officials from NZCS, Treasury and State Services Commission was engaged to undertake a Baseline Review of Customs activities. This included commissioning a pilot study to investigate the suitability of the system dynamics methodology to determine the desired purchase mix for the NZCS. The pilot study was performed on the "Search for Drugs" output group from the Purchase Agreement between the Minister of Customs and the Chief Executive of NZCS. This paper summarises the pilot study and presents a range of system diagrams showing the interrelationships between the inputs, outputs and outcomes associated with the search activity. A lack of suitable data and appropriate outcome measurements precluded the development of a quantitative model. However, the study has provided a framework for strategic analysis at the NZCS.